The effect of the concentration of crosslinkers on the mechanical properties of PEGDA hydrogels - Rabiyatunnisa Binte Ismail (Nanyang Technological University, 2023)
Polyacrylamide (PAAm) hydrogel sheets with varying concentrations of poly(ethylene glycol) diacrylate (PEGDA) as the crosslinker were successfully synthesized via photopolymerization using Irgacure 2959 (I2959) as the photoinitiator. The aim was to study the effects of the crosslinker on the mechanical properties of hydrogels intended for biomedical applications. Fabricated hydrogel sheets were characterized using a tensile test, a swelling test, and a rheology test. The increase in PEGDA concentration resulted in a significant increase in the crosslinking density and Young’s modulus, while causing a significant decrease in the equilibrium water content (EWC). Moreover, from the rheology test results, the increasing concentration of PEGDA in the hydrogel causes the storage modulus (G’) to increase while causing the loss modulus (G”) to decrease.